Evaluating variety and ethephon effect on banana fruit quality at different ripening stages: A comparative and multivariate approach - Laryea, Damian; Supapvanich, Suriyan; Pinsirodom, Praphan; Suwapanich, Rachit; Arsa, Supeeraya; Sirison, Jiraporn (My University, 2025)
The purpose of this study was to investigate the effect variety, ethephon and their interaction may have on banana fruit quality at different ripening stages using comparative and multivariate approach. Three varieties of banana (Musa AAB, Musa AAA, Musa AA) were treated with ethephon (0 mg/kg and 1000 mg/kg), allowed to ripen and analyzed at the fully ripe and overripe stages. Although varieties were significantly different in terms of their peel and pulp colour at the fully ripe and overripe stages, ethephon had no significant effect (p < 0.05) on these qualities except for the lightness (L∗) and whiteness index of the pulp. While variety significantly (p < 0.05) affected the TSS (Total soluble solids), pH, TA (Titratable acidity), TSS/TA ratio and firmness, ethephon only affected the firmness at the fully ripe stage and both firmness and TA at the overripe stage. There were significant differences (p < 0.05) observed among varieties in terms of their total phenols, flavonoids, antioxidant activity (DPPH and FRAP), total sugar and starch at the fully ripe and overripe stages. Ethephon significantly (p < 0.05) increased the total sugar at the fully ripe stage but at the overripe stage it caused a significant (p < 0.05) decrease in both total sugar and FRAP. In most of the quality characteristics assayed, the varieties responded in the same way to the ethephon treatment as shown by the interaction effect. Further multivariate analysis (PCA and HCA) concluded that ethephon treated (1000 mg/kg) samples were not significantly different from untreated (0 mg/kg) samples based on the quality characteristics explored in this study.
Keywords: Antioxidants; Banana ripening; Bioactive compounds; Ethephon; Multivariate approach